User Experience Questionnaire Method In Evaluation And Improved Platform Starup With Kebon Kelapa Region Users - Yogi Saputra; Sucitra Sahara; Rizqi Agung Permana (Fakultas Teknik Universitas Bhayangkara, 2025)
The rapid growth of e-commerce in Indonesia has led to the widespread use of platforms like Shopee among the public. However, it remains unclear how users in specific areas, such as the Kebon Kelapa Subdistrict, perceive their experiences while using the platform. This study aims to evaluate the user experience of Shopee in that area to provide recommendations for improving service quality. This research utilized the User Experience Questionnaire (UEQ), which assesses six aspects: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. Data were collected from active Shopee users in Kebon Kelapa and analyzed quantitatively to determine perception scores for each aspect. The results indicate that, overall, users reported a positive experience, particularly in the areas of Attractiveness, Efficiency, Perspicuity, Dependability, and Stimulation. However, the Novelty aspect received a neutral score, suggesting that Shopee should enhance its innovation in features and interface design. These findings offer valuable insights for Shopee’s development, aiming to create a more inventive, innovative, and engaging platform for its users.